1998
DOI: 10.1016/s0013-4686(97)00241-7
|View full text |Cite
|
Sign up to set email alerts
|

Polynomial model of the inhibition mechanism of thiourea derivatives

Abstract: of Abstract-Interaction of corrosion inhibitors with metal surfaces in acidic solutions was modelled by using a polynomial model based on the Langmuir adsorption isotherm. The curve-fitting procedure yielded a regression equation with a multiple correlation coeficient equal to 0.982. c: 1997 Elsevier Science Ltd

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(41 citation statements)
references
References 10 publications
0
41
0
Order By: Relevance
“…The derived equations are used to predict %IE from the concentrations of the inhibitors and to provide theoretical explanations for the effects of different variables studied [53,54]. In the present work, two models were tested; the linear model and the non-linear models proposed by Lukovits et al for the study of interactions of corrosion inhibitors with metal surface in acidic solutions [53,54]. However, only the linear model produced the best correlation results between experimental and theoretical data.…”
Section: Quantitative Structure Activity Relationship (Qsar)mentioning
confidence: 94%
See 2 more Smart Citations
“…The derived equations are used to predict %IE from the concentrations of the inhibitors and to provide theoretical explanations for the effects of different variables studied [53,54]. In the present work, two models were tested; the linear model and the non-linear models proposed by Lukovits et al for the study of interactions of corrosion inhibitors with metal surface in acidic solutions [53,54]. However, only the linear model produced the best correlation results between experimental and theoretical data.…”
Section: Quantitative Structure Activity Relationship (Qsar)mentioning
confidence: 94%
“…A correlation between quantum chemical parameters and the observed %IE is studied by means of quantitative structure activity relationship (QSAR) approach in which relevant mathematical equations are used to relate the quantum chemical parameters to the observed inhibition efficiency of an inhibitor. The derived equations are used to predict %IE from the concentrations of the inhibitors and to provide theoretical explanations for the effects of different variables studied [53,54]. In the present work, two models were tested; the linear model and the non-linear models proposed by Lukovits et al for the study of interactions of corrosion inhibitors with metal surface in acidic solutions [53,54].…”
Section: Quantitative Structure Activity Relationship (Qsar)mentioning
confidence: 99%
See 1 more Smart Citation
“…Such a procedure represents a challenge to the application of regular structure-activity chemometric thinking applied in biological fields, since the physical adsorption is nonspecific, in opposition to the key-lock mechanism found in molecular biology. Although under such circunstance we should expect lower statistical correlations than those found on biological studies, early corrosion studies, on the contrary, showed several successful results [4][5][6][7][8][9] correlating small number of inhibitors and quantum descriptors.…”
Section: Introductionmentioning
confidence: 74%
“…Lukovits et al 4 employed a polynomial regression analysis for the Langmuir adsorption constant for a set of seven thiourea derivatives obtaining correlations within 0.969-0.982 for R-values with few quantum chemical descriptors. Bentiss et al, 8 based on inhibition efficiency found an excellent correlation between the charge transfer resistance of six triazole and oxadiazole derivatives to three AM1 quantum descriptors.…”
Section: Introductionmentioning
confidence: 99%